Pancreatic islet chromatin accessibility and conformation reveals distal enhancer networks of type 2 diabetes risk - William W. Greenwald (Nature Portfolio, 2019)
Risk loci for type 2 diabetes (T2D) reside in pancreatic islet enhancers. Here, the authors generate high-resolution maps of islet chromatin conformation using Hi-C which they combine with ATAC-seq and ChIP-seq data to annotate candidate target genes of enhancers and validate IGF2BP2 activity in mouse islets.